Optimasi Jalan Pahat Proses Pemesinan CNC Lathe Dan Analisa Biaya Produksi Pembuatan Dead Center Berbantukan CAD/CAM - Saputra, Efrizal; Susilawati, Anita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
CNC is a machining process using a computer program, which one of its function that can arrange toolpath used in NC Code. This study aim is to obtain an optimal toolpath on CNC lathe machining process for making a dead centre. The design of toolpath and simulation to know the time of the process of making dead centre use a software mastercam v9. This research method is done on the rough process of making the geometry shape of the workpiece using 3 schemes of the toolpath. longitudinal, surface to parallel and diametrical . The toolpath consists of two absolute and incremental reference methods. This research revealed the processing time of the scheme for the longitudinal absolute of 22 minutes 43 seconds, the surface to parallel scheme of 22 minutes 45 seconds and the diametrical scheme of 33 minutes 41 seconds. In the incremental scheme the timing process of the longitudinal scheme was 21 minutes 36 seconds, the surface to parallel scheme of 22 minutes 4 seconds and the diametrical scheme of 31 minutes 45 seconds. The fastest time in 3 schemes to making the dead centre was the longitudinal sceme, which used incremental method. the most economical cost for making the dead center using longitudinal incremental . Rp.112.635 and the most expensive using diametrical scheme Rp.116.941.Keyword: Absolute, CNC Lathe, Dead Center, Incremental, Simulation, Toolpath